Importance and outcome relevance of central pathology review in prostatectomy specimens: data from the SAKK 09/10 randomized trial on prostate cancer. (19th January 2017) - Ghadjar, Pirus; Hayoz, Stefanie; Genitsch, Vera; Zwahlen, Daniel R.; Hölscher, Tobias; Gut, Philipp; Guckenberger, Matthias; Hildebrandt, Guido; Müller, Arndt‐Christian; Putora, Paul M.; Papachristofilou, Alexandros; Stalder, Lukas; et al.
Abstract : Objective: To conduct a central pathology review within a randomized clinical trial on salvage radiation therapy (RT) in the presence of biochemical recurrence after prostatectomy to assess whether this results in changes in histopathological prognostic factors, such as Gleason score. Patients and Methods: A total of 350 patients were randomized and specimens from 279 patients (80%) were centrally reviewed by a dedicated genitourinary pathologist. Gleason score, tumour classification and resection margin status were reassessed and compared with the results of local pathology review. Agreement was assessed using contingency tables and Cohen's kappa coefficient. The association between other histopathological features (e.g. largest diameter of carcinoma) and rapid biochemical progression (up to 6 months after salvage RT) was also investigated. Results: There was good concordance between central and local pathology review for seminal vesicle invasion (pT3b: 91%; κ = 0.95 [95% confidence interval CI 0.89, 1.00]), extraprostatic extension (pT3a/b: 94%; κ = 0.82 [95% CI 0.75, 0.89]) and positive surgical margin (PSM) status (87%; κ = 0.7 [95% CI 0.62, 0.79]). The rate of agreement was lower for Gleason score (78%; κ = 0.61 [95% CI 0.52, 0.70]). The median (range) largest diameter of carcinoma was 16 (3–38) mm. A total of 49 patients (18%) experienced rapid biochemical progression after salvage RT. Largest diameter of carcinoma (odds ratio [OR] 2.04 [95% CI 1.30, 3.20]; P = 0.002), resection margin status (OR 0.36 [95% CI 0.18, 0.72]; P = 0.004) and Gleason score (OR 1.55 [95% CI 1.00, 2.42]; P = 0.05) remained associated with rapid progression after salvage RT after backward selection. Conclusion: The results of the central pathology analyses showed concordance between central and local pathology review with regard to seminal vesicle invasion, extraprostatic extension and PSM status, but a lower rate of agreement for Gleason score. Largest diameter of carcinoma was found to be a potential prognostic factor for rapid biochemical progression after salvage RT.